Evaluation of acute and subchronic toxicity of dragon blood resin extract - Saxena, Gaurav; Mittal, Abhilasha; Siddiqui, Abdul Wadood (Journal of Drug Delivery and Therapeutics, 2019)
Draceana cinnabari (Dracaenaceae) is traditionally used in the treatment of wounds, leucorrhea, fractures, and diarrhoea. Herein, we performed a pre-clinical safety evaluation of extract of Draceana cinnabari resin on Spradgue Dawley rats. Toxicological codicil of the extract was carried out following OECD guidelines 423 and 407, with minor changes. DC resin methanol extract administered to the rats by oral gavage at 50, 500, 1500, and 2500 mg/kg body weight daily up to 28 days to male and female rats. Herbal extract could most likely be very much endured up to the dose 2000 mg/kg body weight and could be named Category 4. Oral toxicity studies confirm that Draceana cinnabari has no therapy-related demise or toxic signs on rats. Therefore, the resin, ought to be suitably considered for additional research for its medicinal and therapeutic efficacy. Keywords: Dracaenaceae, DC extract, Resin, Acute toxicity, Sub Chronic Toxicity